Peningkatan Kemampuan Literasi dan Numerasi Siswa SDN 7 Tekolabbua melalui Program Kampus Mengajar Angkatan 4 - Muhamad Hardin Wakila; Abdul Ikhsan; Muh. Iqbal Saleh; Muh. Aryan Firdaus; Maya Permatasari; Nurhaedah Herman; Fiki Fahirah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The Teaching Campus is one of the Ministry of Education and Culture's programmes in the form of Merdeka Belajar-Kampus Merdeka (MBKM) activities. Teaching activities at the Teaching Campus include four aspects; literacy and numeracy activities, technology adaptation and school administration. However, this research is more focused on literacy and numeracy based on the conditions of SDN 7 Tekolabbua, which after initial observations found that the literacy and numeracy skills of SDN 7 Tekolabbua students are still minimal, so this Teaching Campus activity is important to do. This study aims to improve the literacy and numeracy skills of students of SDN 7 Tekolabbua. The research method used is observation and planning of literacy and numeracy support activities. These supporting activities are: implementation of additional classes (maths guidance), revamping the reading corner in each class as well as literacy and numeracy media, procurement of mading, revamping the school library, reading activities for 10-15 minutes before class starts, and reading guidance in the library. The results showed that the implementation of literacy and numeracy support activities during the Teaching Campus programme was able to improve literacy and numeracy skills at SDN 7 Tekolabbua. Students who were previously lacking in literacy and numeracy skills are now showing significant improvements in literacy and numeracy skills, so this 4th batch of campus teaching activities has proven effective in improving the literacy and numeracy skills of students at SDN 7 Tekolabbua.